Kinetic Parameters of Thiolactic Anilide Copper(II) Complex Using TG Analysis - Verma, U.N.; Prasad, S.N.; Kumar, Kunal (Asian Journal of Chemistry, 2016)
Copper(II) sulphate forms a 1 : 2 complex with thiolactic anilide. Kinetic parameters like apparent activation energy, frequency factor, activation entropy and apparent order of reaction second of stage of decomposition of complex have been determined employing the graphical method of Freeman and Carroll, Coat-Redfern and Doyle method as modified by Zsako using non-isothermal TG curves.